2011
DOI: 10.5688/ajpe75225
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Self-directed Learning and Academic Performance in an Abilities Laboratory Course

Abstract: Objective. To assess the relationship between readiness for self-directed learning, academic performance on self-directed learning activities, and resources used to prepare for an abilities laboratory course. Methods. The Self-directed Learning Readiness Scale (SDLRS) was administered to first-year (P1) doctor of pharmacy (PharmD) candidates at the University of Maryland. Additional data collected included final course grades, quiz scores, resources used to prepare for laboratory activities, and demographics.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
2
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 13 publications
2
30
2
13
Order By: Relevance
“…Only 44% of first-year pharmacy students at the University of Maryland achieved a "high" SDL readiness score. 42 This is comparable to results from our study, as only a third of third-year pharmacy students indicated that they would prefer to develop new knowledge through SDL.…”
Section: Discussionsupporting
confidence: 80%
“…Only 44% of first-year pharmacy students at the University of Maryland achieved a "high" SDL readiness score. 42 This is comparable to results from our study, as only a third of third-year pharmacy students indicated that they would prefer to develop new knowledge through SDL.…”
Section: Discussionsupporting
confidence: 80%
“…[22,23] Furthermore, SDLR is required in complex learning situations in which students need to determine their learning needs or choose and implement appropriate learning strategies. [24] Studying in graduate school entails facing complex learning situations. Further, flexible learning systems such as e-learning and night or weekend classes that are increasingly common in graduate schools require an autonomous learning attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Se genera así la necesidad que los docentes deban alentar en los futuros médicos la regulación de sus propias experiencias de aprendizaje, ya que esto sería crucial para sus éxitos futuros [4][5] . El aprendizaje autodirigido toma su base en la andragogía [6][7] , sustentada originalmente por Malcolm Knowles, definiendo a la andragogía como el "arte y ciencia de ayudar a los adultos a aprender", en contraste con la pedagogía concebida como la ciencia de ayudar a aprender a los niños 7,8 . El aprendizaje autodirigido ha sido referido como un proceso de aprendizaje de carácter estratégico y autoreflexivo, en el cual el alumno toma la iniciativa, con o sin la ayuda de otros, para diagnosticar sus necesidades de aprendizaje, formular sus metas, identificar materiales y recursos humanos para aprender, implementar y elegir las estrategias adecuadas y evaluar los resultados de su propio aprendizaje 6,9,10 .…”
unclassified
“…El aprendizaje autodirigido toma su base en la andragogía [6][7] , sustentada originalmente por Malcolm Knowles, definiendo a la andragogía como el "arte y ciencia de ayudar a los adultos a aprender", en contraste con la pedagogía concebida como la ciencia de ayudar a aprender a los niños 7,8 . El aprendizaje autodirigido ha sido referido como un proceso de aprendizaje de carácter estratégico y autoreflexivo, en el cual el alumno toma la iniciativa, con o sin la ayuda de otros, para diagnosticar sus necesidades de aprendizaje, formular sus metas, identificar materiales y recursos humanos para aprender, implementar y elegir las estrategias adecuadas y evaluar los resultados de su propio aprendizaje 6,9,10 . Para implementar esta habilidad se requeriría del uso de estrategias cognitivas, metacognitivas y motivacionales de-pendientes de múltiples factores tanto del alumno, como de los docentes, del sistema educativo e incluso de la propia cultura 3,6,11 .…”
unclassified